The diversity of ground bryophyte communities along an altitudinal gradient on La Réunion island - Lane, Wade Howard (Department of Biological Sciences, 2017)
Aim: To compare the α, β and phylogenetic diversity of the ground bryophyte communities along a tropical altitudinal gradient in order to determine which processes govern these assemblages. Location: La Réunion island (55°39'E; 21 °00'S), in the western Indian Ocean. Methods: The ground bryophyte communities were surveyed along the eastern slope of Piton des Neiges (350 - 3050 m). α, β and phylogenetic diversity along the altitudinal gradient was determined and graphically presented. Results: The α diversity had two distinct peaks at 1150 - 1350 m and at 2750 m, these corresponded to a dominance in liverwort and moss species, respectively. The phylogenetic diversity along the altitudinal gradient was far greater than is predicted from the null models suggesting that ground bryophyte communities are structured according to "environmental filters". The mid-domain effect and mass effect could not be used to describe the changing diversity along the altitudinal gradient, however a correlation analysis revealed temperature and relative humidity influences the changing a diversity. Main Conclusions: In conclusion both ecological and evolutionary processes structure the ground bryophyte communities.